Subtract <math><mstyle displaystyle="true"><mi>a</mi><mi>x</mi></mstyle></math> from both sides of the equation.

Move all terms not containing <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> to the right side of the equation.

Add <math><mstyle displaystyle="true"><mn>5</mn></mstyle></math> to both sides of the equation.

Add <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> and <math><mstyle displaystyle="true"><mn>5</mn></mstyle></math> .

Factor <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> out of <math><mstyle displaystyle="true"><mn>4</mn><mi>x</mi><mo>-</mo><mi>a</mi><mi>x</mi></mstyle></math> .

Factor <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> out of <math><mstyle displaystyle="true"><mn>4</mn><mi>x</mi></mstyle></math> .

Factor <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> out of <math><mstyle displaystyle="true"><mo>-</mo><mi>a</mi><mi>x</mi></mstyle></math> .

Factor <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> out of <math><mstyle displaystyle="true"><mi>x</mi><mo>⋅</mo><mn>4</mn><mo>+</mo><mi>x</mi><mrow><mo>(</mo><mo>-</mo><mi>a</mi><mo>)</mo></mrow></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> by <math><mstyle displaystyle="true"><mn>4</mn><mo>-</mo><mi>a</mi></mstyle></math> .

Divide each term in <math><mstyle displaystyle="true"><mi>x</mi><mrow><mo>(</mo><mn>4</mn><mo>-</mo><mi>a</mi><mo>)</mo></mrow><mo>=</mo><mn>7</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>4</mn><mo>-</mo><mi>a</mi></mstyle></math> and simplify.

Divide each term in <math><mstyle displaystyle="true"><mi>x</mi><mrow><mo>(</mo><mn>4</mn><mo>-</mo><mi>a</mi><mo>)</mo></mrow><mo>=</mo><mn>7</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>4</mn><mo>-</mo><mi>a</mi></mstyle></math> .

Simplify the left side.

Cancel the common factor of <math><mstyle displaystyle="true"><mn>4</mn><mo>-</mo><mi>a</mi></mstyle></math> .

Cancel the common factor.

Divide <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> by <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> .

Simplify <math><mstyle displaystyle="true"><mn>4</mn><mrow><mo>(</mo><mfrac><mrow><mn>7</mn></mrow><mrow><mn>4</mn><mo>-</mo><mi>a</mi></mrow></mfrac><mo>)</mo></mrow><mo>-</mo><mn>5</mn></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mn>4</mn><mrow><mo>(</mo><mfrac><mrow><mn>7</mn></mrow><mrow><mn>4</mn><mo>-</mo><mi>a</mi></mrow></mfrac><mo>)</mo></mrow></mstyle></math> .

Combine <math><mstyle displaystyle="true"><mn>4</mn></mstyle></math> and <math><mstyle displaystyle="true"><mfrac><mrow><mn>7</mn></mrow><mrow><mn>4</mn><mo>-</mo><mi>a</mi></mrow></mfrac></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mn>4</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>7</mn></mstyle></math> .

To write <math><mstyle displaystyle="true"><mo>-</mo><mn>5</mn></mstyle></math> as a fraction with a common denominator, multiply by <math><mstyle displaystyle="true"><mfrac><mrow><mn>4</mn><mo>-</mo><mi>a</mi></mrow><mrow><mn>4</mn><mo>-</mo><mi>a</mi></mrow></mfrac></mstyle></math> .

Simplify terms.

Combine <math><mstyle displaystyle="true"><mo>-</mo><mn>5</mn></mstyle></math> and <math><mstyle displaystyle="true"><mfrac><mrow><mn>4</mn><mo>-</mo><mi>a</mi></mrow><mrow><mn>4</mn><mo>-</mo><mi>a</mi></mrow></mfrac></mstyle></math> .

Combine the numerators over the common denominator.

Simplify the numerator.

Apply the distributive property.

Multiply <math><mstyle displaystyle="true"><mo>-</mo><mn>5</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>4</mn></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mo>-</mo><mn>1</mn></mstyle></math> by <math><mstyle displaystyle="true"><mo>-</mo><mn>5</mn></mstyle></math> .

Subtract <math><mstyle displaystyle="true"><mn>20</mn></mstyle></math> from <math><mstyle displaystyle="true"><mn>28</mn></mstyle></math> .

Do you know how to Solve in Terms of the Arbitrary Variable a y=4x-5 and y=ax+2? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.

Name | one billion two hundred thirty-nine million eight hundred forty-five thousand eight hundred twenty-eight |
---|

- 1239845828 has 32 divisors, whose sum is
**3038008680** - The reverse of 1239845828 is
**8285489321** - Previous prime number is
**89**

- Is Prime? no
- Number parity even
- Number length 10
- Sum of Digits 50
- Digital Root 5

Name | one billion one hundred eighty-one million one hundred twenty-seven thousand three hundred seventy-six |
---|

- 1181127376 has 128 divisors, whose sum is
**7024830624** - The reverse of 1181127376 is
**6737211811** - Previous prime number is
**13**

- Is Prime? no
- Number parity even
- Number length 10
- Sum of Digits 37
- Digital Root 1

Name | three hundred thirty-five million one hundred thirty-five thousand three hundred fifty-nine |
---|

- 335135359 has 8 divisors, whose sum is
**361072880** - The reverse of 335135359 is
**953531533** - Previous prime number is
**3187**

- Is Prime? no
- Number parity odd
- Number length 9
- Sum of Digits 37
- Digital Root 1